Charting domains of silence - a description of a process of feminist training addressing the rape of men in prison - Woodin, Nicola (Department of Psychology, 2016)
The rape of adult males is a subject in need of attention. The rape of men within South African prisons particularly, has been inadequately researched and documented. Investigation is necessary in order to challenge myths which serve to maintain a 'cycle of silence' regarding the male rape, to guide preventative measures, and inform appropriate services. A training programme within Pollsmoor Prison, is described. The initiative addressed the rape of men in prison, upon request of a group of inmates and warders named 'Friends Against Abuse'. This record is a self-reflexive account of a facilitator's experiences of the research and training. It describes a process of reflection and action, its style consistent with the feminist values that informed the work. The methodological blend of Participatory Action Research, Experiential Training, and contributions from psychodynamic thinking, are elaborated. Discussion explores professional and personal challenges to women working within this domain. It raises questions regarding the impact of a feminist agenda on such work and considers issues of sustainability and the impact of similar interventions. Strategies to ensure effective implementation, monitoring and evaluation are suggested, as well as mechanisms to guarantee integrity, such as 'debriefings' and supervision.